Effectiveness of the Child Violence Prevention Program by the Women's Empowerment, Child Protection, and Family Planning Service (DP3AKB) in Bojonegoro Regency - Rupiarsieh, Rupiarsieh; Musta'ana, Musta'ana (JPAP: Jurnal Penelitian Administrasi Publik, 2024)
At the global level, violence against children remains a critical problem that continues to develop each year. Even though Indonesia has regulations governing policies to protect children's rights, the implementation and effectiveness of these regulations are still plagued by numerous gaps and challenges. This study aims to analyze the effectiveness of the child violence prevention program carried out by the Women's Empowerment, Child Protection, and Family Planning Service (DP3AKB) (Indonesian: Dinas Pemberdayaan Perempuan, Perlindungan Anak, dan Keluarga Berencana) in Bojonegoro Regency. This study employs a qualitative research method. Primary data sources, such as interviews and observations, are data collection techniques, while documentation studies serve as secondary data sources. Purposive sampling, which involves establishing criteria, is the technique for identifying informants. We conduct data analysis using interactive data analysis techniques and ensure data validity through source triangulation. The study's results reveal three key indicators that impact the effectiveness of child violence prevention in Bojonegoro Regency: goal achievement, integration, and adaptation. These indicators suggest that the effectiveness of child violence prevention in the region has not been able to meet its objectives due to the annual fluctuations in violence against children. Further research recommendations are that other researchers can analyze collaboration between stakeholders related to the prevention of child violence so that they can produce research with a broader scope.